SIGNAL-AVERAGED ECG AND HEART RATE VARIABILITY IN PATIENTS WITH LEFT VENTRICLE HYPERTROPHY - H. H. Shugushev; V. M. Vasilenko (Российский кардиологический журнал)
The aim of the study was to study the values of singal-averaged ECG and heart rate variability in patients with increased left ventricle mass. We have studied 105 cardiovascular patients. Left ventricle myocardial mass was measured by the method of PENN-convention, SAECG and HRV – with the help of computer complex “Kardiosistema-3”. Depending on the LV mass index, all patients were divided into groups with normal LV mass, concentric and excentric hypertrophy. We have revealed that increased LV mass is followed by increased QRSf and LAS40, decreased RMS and standard RR deviation. These changes closely correlate with the presence of high grade ventricular arrhythmias and can be used as markers of electrical instability of the myocardium in this group of patients.